Effectiveness of Ombudsman of the Republic of Indonesia Supervision in Public Services in Palu City Local Government - Mohammad Iqbal Andi Magga; Daswati; Mohamad Irfan; Erdiyansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The existence of the Ombudsman of the Republic of Indonesia as a public service supervisory institution has a strategic role in encouraging the creation of good service standards. The Ombudsman is mandated to receive public complaints, provide recommendations, and oversee the implementation of public services in accordance with laws and regulations. This research aims to examine and analyze the effectiveness of Ombudsman supervision in public services in Palu City Local Government. This research method uses a qualitative approach with the main data collection technique using in-depth interviews. This research data analysis technique uses an interaction model consisting of data collection, data condensation, data presentation, and conclusion drawing. The results showed that supervision conducted by the Ombudsman played an important role in improving the quality of public services in Palu City, especially in the education and health sectors. The recommendations provided encourage compliance with service standards, although it still faces challenges such as limited resources and low community participation. The effectiveness of supervision can be improved through the use of technology, strengthening coordination with local governments, and a more responsive online complaint system. In addition, positive changes in apparatus behavior can be seen from increased transparency, accountability and professionalism in public services. With a more structured strategy, Ombudsman supervision can continue to encourage higher quality services that are oriented towards the interests of the community